Ballistic Limit of Double Layered Cockleshell Reinforced Carbon Fiber using Numerical Simulation - Siti Nuraisha; Kamarul Azhar Kamarudin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The current study is based on a numerical analysis of a double-layered cockleshell reinforced carbon fibre plate with a ratio of 0.3 (wt%) that was hit by a hemispherical faced bullet. The plate configuration differs between the two models, with the first using a non-spaced double plate and the second using a spaced double plate. Both cockleshell plates have the same material properties. From the simulation results, the ballistic limit velocity and residual velocity for each bullet were compared. In terms of residual velocity, there is no difference between the two models. Same goes to ballistic limit velocity value, there is no difference in ballistic limit velocity for both models. There was a failure of a cockleshell plate. Both models have the same plastic deformation and kinetic energy dissipation, according to the findings. The deformation based on step time is the only difference that can be seen. After complete penetration, the final deformation is still the same. The endpoint of the cockleshell plate subjected to impact by hemispherical face caused major fracture and no plug is ejected. The boundary condition of the cockleshell plate was fractured before the plug could develop, hence no plug formed as a result of the impact.